Implementasi Penilaian Produk Pada Pembelajaran Matematika Berbasis Cooperative Learning Tipe Stad Kelas VIII SMP Muhammadiyah 1 Sukoharjo Tahun 2016/2017 - Luksanatin, Vera Eka; , Dr. Sumardi, M.Si (2017)
This study aims to describe that teachers in SMP Muhammadiyah 1 Sukoharjo already understand about product assessment on learning mathematics-based cooperative learning type STAD, describe the implementation of product assessment in learning mathematics-based cooperative learning type STAD, describe the implementation of product assessment constraints on learning mathematics-based cooperative learning Type STAD. Based on the approach of this research is descriptive qualitative research. The subject of this research is class VIIIA SMP Muhammadiyah 1 Sukoharjo which amounts to 25 students. Data collection techniques using observation, interviews, assignments, tests, and documentation. Validity of data is done by triangulation technique that is by comparing data result from observation, interview, assignment, test, and documentation. Data analysis technique is done by data reduction, data presentation, and data verification and conclusion. Based on the result of research, it can be concluded that: (1) teachers in SMP Muhammadiyah 1 Sukoharjo have not clearly understood the product assessment, so it has not applied in optimum mathematics learning. (2) STAD cooperative learning based product assessment is conducted through the stages of material delivery, group learning, assessment, and team recognition. Implementation of STAD type cooperative learning based product evaluation can increase the activity in discussion, courage in opinion, creativity in making product, so that the average post test of student has increased, because by making product give experience learn to student and can ease in comprehending concept of learning material . (3) obstacles encountered in the study are the students did not pay attention to the explanation of the researcher, the lack of student enthusiasm, the making of the product assessment tool, and the time allocation in implementing the product assessment.